Uji Aktivitas Antioksidan Virgin Coconut Oil (VCO) dengan Penambahan Enzim Papain Menggunakan Metode 1,1 Diphenyl-2-Picryhidrazyl (DPPH) - Aan Nuraini; Riski Dwimalida; Intan Noviarni (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Virgin Coconut Oil (VCO) is derived from fresh coconut meat and can be produced through various methods, including enzymatic processes. This study investigates the effect of adding papain enzyme on the antioxidant activity of VCO. The enzymatic method involves extracting coconut milk with the addition of papain obtained from young papaya. The antioxidant activity was measured using the DPPH method, while other parameters such as moisture content and free fatty acids were also evaluated.The research highlights that VCO is recognized for its health benefits and versatility in various applications. The enzymatic extraction method offers an efficient means of producing VCO while enhancing its properties. This study specifically focuses on how the incorporation of papain influences both the quality of VCO and its antioxidant capacity.In terms of methodology, the study utilized an enzymatic approach for VCO production by incorporating papain into the extraction process. The antioxidant activity was assessed using the DPPH assay, and the resulting VCO was analyzed for moisture content and free fatty acids.The results indicated that VCO produced with papain had a moisture content of 0.22% and free fatty acids of 0.76%, while VCO without enzyme addition showed a moisture content of 0.16%. The antioxidant activity was measured at 18.35 ppm for VCO with papain, compared to 13.51 ppm for pure VCO.In conclusion, the addition of papain enzyme not only accelerated the production of VCO but also enhanced its antioxidant activity, classifying both types of VCO as having strong antioxidant properties. However, it is important to note that the moisture content and free fatty acids in VCO with enzyme addition did not meet the Indonesian National Standard (SNI 7381:2008), likely due to residual water from the papaya fruit.